Bidirectional Influences Between Dimensions of Coparenting and Adolescent Adjustment - Riina, Elizabeth M. (2013)
Research on coparenting documents that mothers' and fathers' coordination and mutual support in their parenting roles is linked to their offspring's adjustment in childhood, but we know much less about the coparenting of adolescents. Taking a family systems perspective, this study assessed two dimensions of coparenting, parents' shared decision-making and joint involvement in activities with their adolescents, and examined bidirectional associations between these coparenting dimensions and boys' and girls' risky behaviors and depressive symptoms across four time points (6 years) in adolescence. Participants were 201 mothers, fathers, and adolescents (M = 11.83, SD = .55 years of age at Time 1; 51 % female). Parents of sons shared more decisions, on average, than parents of daughters. On average, shared decision-making followed an inverted U shaped pattern of change, and parents' joint involvement in their adolescents' activities declined. Cross-lagged findings revealed that risky behavior predicted less shared decision-making, and shared decision-making protected against increased risky behavior for boys. For girls and boys, parents' joint involvement predicted fewer risky behaviors, and lower levels of risky behavior predicted higher levels of joint involvement. In contrast, boys' and girls' depressive symptoms predicted less joint involvement. The discussion centers on the nature and correlates of coparenting during adolescence, including the role of child effects, and directions for future research on coparenting during this developmental period.